Low -load pathogen spillover predicts shifts in skin microbiome and survival of a terrestrial-breeding amphibian - Becker, C. Guilherme; Bletz, Molly C.; Greenspan, Sasha E.; Rodriguez, David; Lambertini, Carolina; Jenkinson, Thomas S.; Guimaraes, Paulo R.; Assis, Ana Paula A.; Geffers, Robert; Jarek, Michael; Toledo, Luis Felipe; Vences, Miguel; et al. (Royal Soc, 2019)
Wildlife disease dynamics are strongly influenced by the structure of host communities and their symbiotic microbiota. Conspicuous amphibian declines associated with the waterborne fungal pathogen Batrachochytrium dendrobatidis (Bd) have been observed in aquatic-breeding frogs globally. However, less attention has been given to cryptic terrestrial-breeding amphibians that have also been declining in tropical regions. By experimentally manipulating multiple tropical amphibian assemblages harbouring natural microbial communities, we tested whether Bd spillover from naturally infected aquatic-breeding frogs could lead to Bd amplification and mortality in our focal terrestrial-breeding host: the pumpkin toadlet Brachycephalus pitanga. We also tested whether the strength of spillover could vary depending on skin bacterial transmission within host assemblages. Terrestrial-breeding toadlets acquired lethal spillover infections from neighbouring aquatic hosts and experienced dramatic but generally non protective shifts in skin bacterial composition primarily attributable to their Bd infections. By contrast, aquatic-bleeding amphibians maintained mild Bd infections and higher survival, with shifts in bacterial microbiomes that were unrelated to Bd infections. Our results indicate that Bd spillover from even mildly infected aquatic-breeding hosts may lead to dysbiosis and mortality in terrestrial-breeding species, underscoring the need to further investigate recent population declines of terrestrial-breeding amphibians in the tropics.
Keywords: Batrachochytrium dendrobatidis; chytridiomycosis; community composition; host microbiome; direct development